Detection of phytoplasma associated with witches broom of Dendrocalamus strictus Nees by polymerase chain reaction - and M. KRISHNA REDDY2*, V. SURYANARAYANA1*, H. PRADEEP KUMAR1 (Indian Phytopathology, 2009)
Infected tissues of Dendrocalamus strictus Nees plants showing witches broom symptoms were screened for the presence of the phytoplasma infection using Polymerase Chain Reaction. Oligonucleotide primers specific to the conserved region of 16S- 23S r RNA amplified 537bp sequence of the phytoplasma. Restriction analysis of PCR amplified DNA with Rsa I and Hae II showed banding pattern similar to group 16SrXIV phytoplasma. The results indicated Dendrocalamus strictus witches broom phytoplasma belongs to group XIV Bermuda grass White leaf group phytoplasma.